Revaloración de activos fijos, su efecto en la situación financiera y su correcta presentación para la toma de decisiones en la Municipalidad Distrital del Yavari, periodo - 2019 - Sánchez Alvarado, Auri Margaret (2022)
This research work entitled: "Revaluation of fixed assets, its effects on financial information and its correct presentation for decision-making in the Yavarí District Municipality, period 2019", corresponding to the finance research line, has had the objective to evaluate the application of the revaluation of fixed assets through technical studies, in order to correct and improve the reasonableness of financial information in decision making. The research is of a documentary type, with a quantitative approach, the results were obtained based on a sample consisting of 4 employees of the Patrimonial Assets Maintenance and Auxiliary Services unit, the technique used being the survey, which was prepared and applied through the questionnaire, with the aim of collecting information to establish an analysis of the results. From the collection of information and analysis of results, it has been concluded that the public entity does not comply with applying the process of revaluation of fixed assets of its property; there are no supporting documents that accredit or evidence the revaluations made; that officials do not effectively comply with current legal provisions; officials recognize that they have a certain responsibility for failing to fulfill their duties; the entity has fully depreciated fixed assets, which are still operating and providing good service; there are updated documents of the awards and/or donations received; Finally, some officials maintain that there are public infrastructures pending legal physical sanitation.